Implementation of medication-related indicators of potentially preventable hospitalizations in a national chronic disease management program for older patients with multimorbidity. (18th June 2018) - Caughey, Gillian E; Hillen, Jodie B; Bacon, Stephanie; Bullock, Nicholas; Bullock, Virginia; Kalisch Ellett, Lisa
Abstract: Initial assessment: Older people are at increased risk of medication-related potentially preventable hospitalizations (MR-PPH) due to the presence of multiple chronic conditions (multimorbidity) and subsequent polypharmacy. Choice of solution: A pilot study was conducted, using evidence-based indicators to detect older patients in a chronic disease management program (CDMP) at risk of hospitalization due to sub-optimal medication use. Implementation: Previously validated indicators for MR-PPH were applied to patients with multimorbidity, aged 65 years or older and who were enrolled in a national community-based CDMP. Nurse-led telephone interviews and case note abstraction were used as data sources. Evaluation: Nineteen patients triggered the MR-PPH indicators 85 times with a median of four per patient. Sub-optimal medication management was identified 34 times (40%) with a median of two per patient. The most common reasons for sub-optimal medication management were exposure to medications associated with falls, underuse of angiotensin-converting enzyme inhibitor/angiotensin-2 receptor blocker medications for cardiovascular disease and low rates of hemoglobin A1c and renal monitoring in patients with diabetes. Lessons learned: This study has shown the utility of MR-PPH indicators within a CDMP to identify and monitor sub-optimal medication-related care. Implementation and ongoing monitoring of these types of indicators can support the development of targeted programs to reduce the ongoing risk of adverse events in the older population and improve the overall quality of life.